2009
DOI: 10.1021/cm9013267
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Layer Deposition of Hybrid Organic−Inorganic Alucone Polymer Films Using a Three-Step ABC Reaction Sequence

Abstract: Thin film growth using molecular layer deposition (MLD) or atomic layer deposition (ALD) is based on sequential, self-limiting surface reactions. In this work, MLD is used to grow a hybrid organic−inorganic polymer film based on a three-step ABC reaction sequence using trimethylaluminum (TMA), ethanolamine (EA), and maleic anhydride (MA) as the reactants. This three-step ABC sequence avoids the use of homobifunctional organic precursors by employing a homotrifunctional inorganic reactant (TMA), a heterobifunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
136
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(144 citation statements)
references
References 34 publications
6
136
2
Order By: Relevance
“…A strong methane signal was seen during the TMA and EA doses, and only a small amount of methane was seen during the MA dose. This is consistent with the proposed surface reactions during the ABC alucone growth by Yoon et al [12], as shown in Eqs. (1)-(3).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A strong methane signal was seen during the TMA and EA doses, and only a small amount of methane was seen during the MA dose. This is consistent with the proposed surface reactions during the ABC alucone growth by Yoon et al [12], as shown in Eqs. (1)-(3).…”
Section: Resultssupporting
confidence: 93%
“…It is expected that porous oxide films obtained from organic precursors with longer carbon chains should have larger pores, which would improve catalytic activity relative to the films prepared in the previous study. Yoon et al reported the fabrication of alucone polymer films based on a three-step ABC reaction sequence using TMA, ethanolamine (EA), and maleic anhydride (MA) as the reactants [12]. There is no report for the alucone ABC MLD on particles at large quantities and the formation of porous metal oxide films from ABC MLD films.…”
Section: Introductionmentioning
confidence: 99%
“…There are a growing number of reports on various hybrid thin films fabricated with ALD/MLD, [6][7][8][9][10][11][12][13][14][15][16] but the focus has primarily been on homogeneous 1:1 inorganic-organic hybrid materials where single layers of the organic constituent alternate with single layers of the inorganic part, and then also on so-called nanolaminate structures built up of considerably thicker layers of the two constituents. Despite the potential usefulness of superlattices consisting of very thin layers of one material between thicker layers of another, there are very few reports of the fabrication of hybrid superlattices using ALD/MLD.…”
Section: Introductionmentioning
confidence: 99%
“…An exciting development in ALD is to extend the layerby-layer heterogeneous molecular assembly reaction mode into synthesizing highly conformal ultrathin films of different classes of materials including organic, 123,124 organicinorganic hybrid, [124][125][126][127][128][129][130] and porous coatings. 125,129 This development would open up great yet-to-explored opportunities to organize organic and/or inorganic components in a vector mode for desired electron and charge transfer properties, 23 chemical properties, 123 and structural properties.…”
Section: B Exploring New Ald Processesmentioning
confidence: 99%
“…125,129 This development would open up great yet-to-explored opportunities to organize organic and/or inorganic components in a vector mode for desired electron and charge transfer properties, 23 chemical properties, 123 and structural properties. 125,129 Owing to the low deposition temperature of many ALD processes, it has also been demonstrated that ALD could be applied to organic substrates such as polymers [131][132][133] and biomaterials, 134 which provides another degree of flexibility for engineering materials of interest in electrochemical applications.…”
Section: B Exploring New Ald Processesmentioning
confidence: 99%